DEVELOPMENT OF FASCIOLA HEPATICA AND ITS BIOTIC POTENTIAL IN RATTUS NORVEGICUS HOLTZMAN - Iturbe Espinoza, Paul (2013)
Fasciola hepatica is a digenean that has a complex life cycle which includes a vertebrate host in which its sexual reproduction occurs, verifiable in experimental animals. The objective of this study was to estimate the invasive power (PI), extension invasion (EI) and the biotic potential of this digenean in Rattus norvegicus albinus Holtzman strain, infected experimentally with F. hepatica's metacercariae which was obtained from infected snails in nature, in two provinces. Twenty metacercariae were administered in semisolid diet to six specimens of R. norvegicus, which were maintained in bioterio under controlled environmental conditions. We made coproparasitological analysis by simple concentration and sedimentation technique from the 86 to 100 days post infection and then proceeded with necropsies. We observed that the average production of eggs by adult F. hepatica was 9135.70 ± 2196.8, invasive power from 6.67 to 8.33% and the extent of invasion of 66.67% in R. norvegicus.